Safety Analysis Reports of First-Of-A-Kind Nuclear Reactors in Brazil: Proposal of Content for Deterministic Safety Analysis - Nelson Luiz Dias Ferreira; Claudia Giovedi; Mike Modro; Alessandro Petruzzi (Brazilian Journal of Radiation Sciences, 2025)
The main documents of Licensing processes for nuclear reactors in Brazil are the Preliminary Safety Analysis Report (PSAR), in the construction phase, and the Final Safety Analysis Report (FSAR), in the operation phase (initial and permanent), as defined by the National Nuclear Energy Commission (CNEN). Thus, this paper presents a proposal for the format and content of the Deterministic Safety Analysis (DSA) chapter of Safety Analysis Reports (SAR) of First-Of-A-Kind (FOAK) nuclear reactors in Brazil, such as Small Modular Reactors (SMR), based on the combination of recommendations of United States Nuclear Regulatory Commission (USNRC) and International Atomic Energy Agency (IAEA) normative and documentary basis. Documentation from the USNRC applies to Nuclear Power Plants (NPPs), specifically to Light Water Reactors (LWR); complementary, IAEA documentation outlines a format and content of a SAR for NPPs but it may, in parts, have a wider applicability to other nuclear facilities. Compared to what is recommended by the USNRC, the IAEA allows for greater scope in terms of the types of events to be considered in a DSA, such as, for example, the Design Extension Conditions (DEC) and, in terms of methodology, it allows for a greater number of options for DSA approaches. The content proposal presented in this work recommends the consideration of DEC without significant fuel degradation (DEC-A), the adoption of the combined approach, analysis of hazards and Pressurized Thermal Shocks (PTSs) analysis, among others.